Identification of a Predominantly Interferon-λ-Induced Transcriptional Profile in Murine Intestinal Epithelial Cells - Selvakumar, Tharini A.; Bhushal, Sudeep; Kalinke, Ulrich; Wirth, Dagmar; Hauser, Hansjörg; Köster, Mario; Hornef, Mathias W. (Frontiers in Immunology, 2017)
Type I (α and β) and type III (λ) interferons (IFNs) induce the expression of a large set of antiviral effector molecules via their respective surface membrane receptors. Whereas most cell types respond to type I IFN, type III IFN preferentially acts on epithelial cells and protects mucosal organs such as the lung and gastrointestinal tract. Despite the engagement of different receptor molecules, the type I and type III IFN-induced signalling cascade and up-regulated gene profile is thought to be largely identical. Here we comparatively analysed the response of gut epithelial cells to IFN-β and IFN-λ2 and identified a set of genes predominantly induced by IFN-lambda2. We confirm the influence of epithelial cell polarization for enhanced type III receptor expression and demonstrate the induction of predominantly IFN-lambda2 induced genes in the gut epithelium in vivo. Our results suggest that IFN-lambda2 targets the epithelium and induces genes to adjust the antiviral host response to the requirements at mucosal body sites.